Recensión del Libro “El Emprendedor de Éxito” de Rafael Alcaraz - Salas León, Carlos (2021)
How to formulate a business plan and become a successful entrepreneur along the way Rafael Alcaraz Rodríguez holds a PhD in Economics and Business Administration from Deusto Business School, Spain. He is also a professor, researcher, trainer and consultant in the areas of Leadership and High Performance Teams, Entrepreneurship and New Business Development, Family Businesses and Competency Development at the Instituto Tecnológico y de Estudios Superiores de Monterrey (ISTEM). Alcaraz Rodriguez, with the sponsorship of MC Graw Hill publishing house, delivers the book "The Successful Entrepreneur", in its sixth edition. This book introduces the reader in an orderly and systematic manner to the process of planning, formulation, execution and evaluation of the business project until it becomes a real company. The structure of the book, designed in 15 chapters and 328 pages, provides the student with the tools to develop an entrepreneurial plan in the creation of a new company, innovative project or social enterprise; for which each chapter becomes a guide to contribute in the structuring of a business plan.